An Unusual Site of Adenomatoid Odontogenic Tumor Presenting as Periapical (Radicular) Cyst: A Rare Case Report - C Anand Kumar; Jagat Reddy; Siddharth Gupta; Namita Raghav; 5MunBhawni Bagga (Wolters Kluwer Medknow Publications, 2010)
The adenomatoid odontogenic tumor is a rare odontogenic tumor often misdiagnosed as an odontogenic cyst, constituting only 3% of all odontogenic tumors. Though odontogenic in origin but it appeared as duct like structures, often interspersed throughout the lesion which gives a glandular, i.e. Adenomatoid appearance. Here we are presenting a rare case report of an unusual site of extrafollicular adenomatoid odontogenic tumor in the mandible w.r.t 32, 33, 34 and 35 mimicking periapical disease clinical and radiographically. However, diagnosis of adenomatoid odontogenic tumor should be considered when the clinician is presented with a corticated radiolucency in the anterior lower jaw, especially in teens and young adults.